Earnings over the Life Course: General versus Vocational Education - Bart H.H. Golsteyn; Anders Stenberg (Institute of Labor Economics (IZA), 2017)
Two common hypotheses regarding the relative benefits of vocational versus general education are (1) that vocational skills enhance relative short-term earnings and (2) that general skills enhance relative long-term earnings. Empirical evidence for these hypotheses has remained limited. Based on Swedish registry data of individuals in short (2-year) upper secondary school programs, this study provides a first exploration of individuals' earnings across nearly complete careers. The descriptive earnings patterns indicate support for both hypotheses (1) and (2). The support holds when controlling for GPA and family fixed effects and also when taking into account enrolment in further education and fertility decisions.
Keywords: J24; J64; J31; I20; 330; human capital; vocational education; life cycle; tracking